Knowledge Production in a Territorial Network of Organizations: Identifying the Determinants in the Case of Moroccan Technopole - Adriana Burlea-Schiopoiu; Zineb Znagui (Administrative Sciences, 2024)
Globalization has led to a geographical concentration of economic activities, known as territorialized networks of organizations, especially technopoles. That is why the knowledge process takes on new dimensions and requires a multidimensional and dynamic approach. This study aims to analyze factors of knowledge production dynamics in technopoles based on a conceptual model that is elaborated based on the literature review and tested in a technopole’s environment, knowledge creation, knowledge transfer, and knowledge utilization processes. We used partial least squares structural equation modeling confirmatory composite analysis techniques to test the validity and reliability of the model. The technopole actors’ heterogeneous nature allowed us to use a stratified sampling technique. The data were collected from 303 respondents from four technopoles in Morocco. Our findings indicate the existence of a strong influence of the factors presented in the research model on knowledge production dynamics in technopoles. Moreover, the technopole actors’ contribution to the creation, transfer, and utilization of knowledge is more likely to be effective in increasing knowledge production dynamics within the network. The technopoles are likely to be more successful in regions that have the properties of a large, diversified, and well-established metropolitan economy, a robust research base, and an entrepreneurial culture where stakeholders are actively engaged. Our study is the first to analyze the dynamics of knowledge production in Moroccan territorialized networks of organizations (i.e., technopoles). This study provides insights to managers in formulating efficient knowledge production strategies in technopoles and offers suggestions at three levels: actors of technopoles, technopoles, and regional actors.